Alternative genomic diagnoses for individuals with a clinical diagnosis of Dubowitz syndrome. Issue 1 (24th October 2020) - Dyment, David A.; O'Donnell‐Luria, Anne; Agrawal, Pankaj B.; Coban Akdemir, Zeynep; Aleck, Kyrieckos A.; Antaki, Danny; Al Sharhan, Hind; Au, Ping‐Yee B.; Aydin, Hatip; Beggs, Alan H.; Bilguvar, Kaya; Boerwinkle, Eric; et al.
Abstract: Dubowitz syndrome (DubS) is considered a recognizable syndrome characterized by a distinctive facial appearance and deficits in growth and development. There have been over 200 individuals reported with Dubowitz or a "Dubowitz‐like" condition, although no single gene has been implicated as responsible for its cause. We have performed exome (ES) or genome sequencing (GS) for 31 individuals clinically diagnosed with DubS. After genome‐wide sequencing, rare variant filtering and computational and Mendelian genomic analyses, a presumptive molecular diagnosis was made in 13/27 (48%) families. The molecular diagnoses included biallelic variants in SKIV2L, SLC35C1, BRCA1, NSUN2 ; de novo variants in ARID1B, ARID1A, CREBBP, POGZ, TAF1, HDAC8, and copy‐number variation at1p36.11( ARID1A ), 8q22.2( VPS13B ), Xp22, and Xq13( HDAC8 ). Variants of unknown significance in known disease genes, and also in genes of uncertain significance, were observed in 7/27 (26%) additional families. Only one gene, HDAC8, could explain the phenotype in more than one family ( N = 2). All but two of the genomic diagnoses were for genes discovered, or for conditions recognized, since the introduction of next‐generation sequencing. Overall, the DubS‐like clinical phenotype is associated with extensive locus heterogeneity and the molecular diagnoses made are for emerging clinical conditions sharing characteristic features that overlap the DubS phenotype.